Os sentidos sociais da velhice e do envelhecimento nos programas de preparação para aposentadoria de grandes empresas brasileiras - Bernardinelli, Ingrid (Universidade Federal de São Carlos, 2020)
In recent years, the number of large companies that have implemented retirement preparation programs has increased, which stems from their perception of demographic changes and the need for intervention in their employees' retirement processes. The objective of the research is to analyze the social conceptions of old age and aging underlying the retirement preparation programs of Brazilian companies. To achieve the proposed objective, a qualitative research, focused on analyzing, investigating and incorporating the meanings and interpretations attributed to the programs and the individuals involved, was carried out. Using secondary data about management literature and reports published in the business media, and primary data, collected through semi-structured interviews with consultants that rely on these programs and Brazilian companies. These data were analyzed based on the technique of content analysis. The concept of old age underlying the programs has been shown to be positive, since it agrees with a more active retirement. This transformation is in line with analyzes that point to recent ideological transformations that value the idea of activity and the financialization process. Corporate retirement preparation programs encourage an investment culture, of which the topic of financial planning is highlighted. Such programs spread as an opportunity to engage in new activities after retirement, such as economic activities and entrepreneurial activities, and with that, builds new perspectives for retirement. The understanding of the meanings underlying these programs is relevant, since large companies and consultancies are influential actors in the construction of meanings about old age and aging, influencing the ways in which society in general understands the phenomenon and influencing the ways that many people plan for retirement, deconstructing old-fashioned views of old age and rebuilding it as a new, more active phase.
The social meanings of old age and aging in the retirement preparation programs of large Brazilian companies
Keywords: Velhice; Significado social; Programa de preparação para a aposentadoria; Cultura e Organizações; Old age; Social meaning; Retirement preparation program; Culture and Organizations; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DO BEM-ESTAR SOCIAL::ECONOMIA DOS PROGRAMAS DE BEM-ESTAR SOCIAL; OUTROS